Kim Jong-un's Byungjin Policy: Support or obstacle for economic convergence on the Korean peninsula? - Ralph Wrobel (OrdnungsPolitisches Portal (OPO), 2021)
Transformation to some market approaches in North Korea is of highest importance for more economic cooperation on the Korean peninsula. Kim Jong-uns's Byungjin policy, a new ideological approach announced in 2011, gave some hope for such reforms. At least, basic economic reforms like in China or Vietnam in the 1980s would be helpful. Both countries started with reforms in the agricultural sector and management reforms in the industry. Additionally, they opened up their countries to the capitalist world by Special Economic Zones (SEZs). Especially since introduction of Byungjin Policy by Kim Jong-un North Korea followed these reform steps obviously. But while reforms in agriculture and management of State-Owned Enterprises are quite similar to China or Vietnam a lack of institutionalization must be stated. As a result, only informal markets ("jangmadang") evolved in North Korea. Also, a new group of entrepreneurs ("donju") - people investing money without any legal security - came into existence. Additionally, even though SEZs have been established in North Korea a real opening to foreign investors and clients cannot be observed. There are two main reasons for this: First, ideology is much more crucial for the North Korean regime than for the communist parties in China or Vietnam. Ideological approaches like Juche or Songun still have a religious significance and thereby the function to stabilize the regime. Also, UN sanctions hinder more foreign trade and investment. Therefore, Kim Jong-un is trapped between short-term ideology-based regime stability and nuclear armament on the one hand and economic reforms bringing some regime stability in the long term.
Keywords: 330; North Korea; Economic Reforms; informal institutions; Juche ideology; Byungjin ideology